Firms' Home-market Relationships: Their Role when Selecting International Alliance Partners - Elg, Ulf (Journal of International Business Studies, 2000)
The importance of taking account of a firm's home-market relationships in efforts to explain its choice of partners for international alliances is discussed. Liberating and moderating relationships are proposed as two alternative types of alliances that firms may form in response to the influence of home market dependencies. Propositions suggesting explanatory factors that predict which type of relationship is formed then are presented; these propositions are based on the complementary aspects of transaction cost theory, the network approach, and resource dependence theory.